Toward a Certification Framework for TV 3.0: Building Trust in the Ecosystem - Moreno, Marcelo F. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
The transition from TV 2.x to TV 3.0 shifts the digital television ecosystem from middleware-mediated interactivity to an application-oriented platform, where broadcaster applications and cross-layer orchestration are central to new business models and user experiences. This evolution makes interoperability and reliability prerequisites, exposing the insufficiency of the self-certification model that characterized TV 2.x. We argue for the establishment of a network of accredited laboratories, coordinated by INMETRO and ANATEL, hosted in universities, and supported by industry contributions. Beyond technical assurance, it would foster broadcaster trust, enable new commercial opportunities, and serve the public interest, while simultaneously advancing research, innovation, and professional training in digital television.